2017
DOI: 10.1111/obr.12497
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles and body mass index: a systematic review of prospective studies among children

Abstract: Background Parenting style may be an important determinant of an individual's future weight status. However, reviews that evaluate the relationship between parenting style and weight-related outcomes have not focused on prospective studies. Methods We systematically searched PubMed, Embase, and PsychInfo for studies published between 1995-2016 that evaluated the prospective relationship between parenting style experienced in childhood and subsequent weight outcomes. Results We identified eleven prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 56 publications
9
61
2
4
Order By: Relevance
“…This attempt to exert excessive control could be witnessed in the high levels of EOI and CC reported by the OG mothers in the present study. Furthermore, these findings are in line with a systematic review that found a significant relation between authoritarian parents, who demonstrated greater control and demandingness, and higher BMI in their children (Sokol, Qin, & Poti, ). However, no differences were found in the other family functioning variables (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…This attempt to exert excessive control could be witnessed in the high levels of EOI and CC reported by the OG mothers in the present study. Furthermore, these findings are in line with a systematic review that found a significant relation between authoritarian parents, who demonstrated greater control and demandingness, and higher BMI in their children (Sokol, Qin, & Poti, ). However, no differences were found in the other family functioning variables (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Parenting style in general and relation to feeding practices has also been studied in PO. Findings support the theory that authoritative parenting practices, in which parents prioritize what they believe is in their child's best interest while also accommodating some degree of child preferences, are optimal relative to authoritarian or permissive parenting styles and are associated with lower child body mass index (BMI) and increased consumption of healthier foods (Kakinami, Barnett, Seguin, & Paradis, ; Kiefner‐Burmeister, Hoffmann, Zbur, & Musher‐Eizenman, ; Langer, Seburg, JaKa, & Sherwood, ; Shloim, Edelson, Martin, & Hetherington, ; Sokol, Qin, & Poti, ). In fact, parental monitoring may have a curvilinear relationship with children's dietary behaviours whereby it is increasingly health‐promoting only up to a certain level, beyond which it becomes counterproductive (Vaughn et al, ).…”
Section: Introductionsupporting
confidence: 53%
“…Authoritarian parenting, characterized by high demands and expectations but low responsiveness and support, is prospectively related to extreme weight control and binge eating behaviors compared to other parenting styles [42]. Conversely, authoritative parenting styles, characterized by high expectations and well as high responsiveness and support, are protective against obesity development [43]. Furthermore, family connectedness, such as feeling loved and having easy communication with a parent, is protective against disordered eating development in children with obesity [9].…”
Section: Correlates Of Dysfunctional Eating In Children With Obesitymentioning
confidence: 99%